Maternity services for rural and remote Australia: barriers to operationalising national policy. Issue 11 (November 2017) - Longman, Jo; Kornelsen, Jude; Pilcher, Jen; Kildea, Sue; Kruske, Sue; Grzybowski, Stefan; Robin, Sarah; Rolfe, Margaret; Donoghue, Deborah; Morgan, Geoffrey G.; Barclay, Lesley
Highlights: National policy intends woman-centred rural maternity services should continue. A considerable gap exists between this intent and services at local level. Barriers to operationalising this intent include lack of leadership and workforce planning. Barriers to operationalising policy intent may be eased by using a planning Toolkit. Abstract: Introduction: In Australia, many small birthing units have closed in recent years, correlating with adverse outcomes including a rise in the number of babies born before arrival to hospital. Concurrently, a raft of national policy and planning documents promote continued provision of rural and remote maternity services, articulating a strategic intent for services to provide responsive, woman-centred care as close as possible to a woman's home. The aims of this paper are to contribute to an explanation of why this strategic intent is not realised, and to investigate the utility of an evidence based planning tool (the Toolkit) to assist with planning services to realise this intent. Methods: Interviews, focus groups and a group information session were conducted involving 141 participants in four Australian jurisdictions. Field notes and reports were thematically analysed. Results: We identified barriers that helped explain the gap between strategic intent and services on the ground. These were absence of informed leadership; lack of knowledge of contemporary models of care and inadequate clinical governance; poor workforce planning and use of resources; fallacious perceptions of risk; and a dearth of community consultation. In this context, the implementation of policy is problematic without tools or guidance. Conclusions: Barriers to operationalising strategic intent in planning maternity services may be alleviated by using evidence based planning tools such as the Toolkit.